Single-subject methodology: an alternative approach - Bates, B. T. (Medicine & Science in Sports & Exercise, 1996)
The purpose of this paper is to identify and discuss an alternative experimental methodology, single-subject (SS) design. The primary premise for SS analyses forms the basis for many research questions in areas such as movement/motor control, individual performance patterns/strategies, and injury mechanisms. A brief historical perspective elucidating the evolution of modern-day group statistical techniques and the relationship to the individual is presented. Rationale for the SS design within this context is also discussed. Specific statistical applications include mean comparison tests (ANOVA, Model Statistics), correlation, and multiple regression. Validation of the underlying statistical assumptions of independence and normality relative to the applications are briefly discussed. Finally, several examples are included.